Kajian Optimalisasi Pemanfaatan Csr Untuk Kegiatan Produktif Dalam Upaya Meningkatkan Kesejahteraan Masyarakat Di Provinsi Kalimantan Tengah - Muhamad Yusuf; Raden Biroum Bernandianto; Farid Zaky Yopiannor; Muhammad Jailani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This research aims to families the optimization of CSR for productive activities in the effort to increase the Community's welfare in the province of Central Kalimantan. This study is done because Pemerinah aware will not be able to finance all development activities with the economic growth that is not maximized. That is the increase of government and private cooperation that is more systematic and sustainable need to be flown and optimized for misalignment through the scheme of fund-raising of Corporate Social responsibility (CSR). This study uses a qualitative method approach that is supported by quantitative data. The qualitative approach is assumed to be relevant to capture the entire stakeholder's view of CSR. The study will take East Kotawarakan regency as the object of study. East Kotawarwants Regency already has a Perda that regulates CSR and institutional of CSR Forum. The selection of the object of this study is also based on some practical considerations related to the potential availability and access to data and many of the companies in the East Kotawarwants regency in the Central Kalimantan provincial government environment. The results of this study showed the CSR policy by the East Kotawarwants District government in the implementation of weak. This is due to the lack of understanding between stakeholders in understanding good and sustainable CSR governance. The mandate from local regulation No. 21, 2014 Regency of Kotawarwant Timut about CSR is the establishment of CSR Forum. However, in its journey, the CSR forums have not been able to move flexibly due to limited employment and budget programs. So that the CSR Forum until now can not optimally bridge the government with the company related to the governance of the CSR program.